2022
DOI: 10.1002/ppul.26057
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculous bronchial stenosis: Diagnosis and role of interventional bronchoscopy

Abstract: The reported prevalence of tuberculous bronchial stenosis in children is unknown and rarely reported in English-speaking literature. In adult patients with pulmonary tuberculosis, it varies from 40% in an autopsied series in the preantibiotic era to 10% in patients who have undergone routine bronchofibroscopy in modern times. We describe our experience of four cases of confirmed bronchial stenosis due to MTB collected between January 2000 and June 2021 in this case series descriptive study.The diagnosis of bro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Studies have suggested an inflation time between 30 and 60 seconds in clinical practice, depending on individual circumstances. 13 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have suggested an inflation time between 30 and 60 seconds in clinical practice, depending on individual circumstances. 13 …”
Section: Discussionmentioning
confidence: 99%
“…Studies have suggested an inflation time between 30 and 60 seconds in clinical practice, depending on individual circumstances. 13 Cryotherapy is the use of extreme cold to freeze, destruct and remove abnormal tissue, damaging intracellular organelles, and the cell wall, and in the process trigger the body's repair and regeneration process. 14 Cryotherapy is applicable to bronchial stenosis caused by granuloma formation in the proliferative phase of tracheobronchial TB.…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact pathogenesis of EBTB is unknown, possible mechanisms include (1) direct seeding from the parenchymal focus, (2) erosion from a nearby lymph node, (3) hematogenous, or (4) lymphatic spread. 3 With FB, the lesion appears as either mucosal inflammation, ulceration, caseation, tumorous growth, or stenosis, depending on the subtype. 5 Therapeutic targets of EBTB include eradication of TB bacilli and maintaining airway patency.…”
mentioning
confidence: 99%
“…Although common in adults, literature is sparse regarding the use of interventional bronchoscopic techniques in pediatric EBTB. 3,4 Here, we present our experience, a series of six cases of EBTB, presenting at various stages that were diagnosed and managed in our tertiary care pediatric pulmonology unit. This is a retrospective descriptive study.…”
mentioning
confidence: 99%
See 1 more Smart Citation